Employee Performance at PT Agri First Indonesia in Relation to Organisational Culture and Organisational Commitment - Rasmulia Sembiring (Jurnal Info Sains : Informatika dan Sains, 2023)
The objective of this study is to examine the impact of organisational culture and organisational commitment on employee performance within the context of PT Agri First Indonesia. The importance of organisational culture and organisational commitment on employee performance in a business setting has been widely recognised. The research methodology employed in this study adopts a quantitative approach, utilising data gathering techniques in the form of questionnaires issued to staff working in the Human Resource Development (HRD) department at PT Agri First Indonesia. The data that has been gathered will be subjected to regression analysis methods in order to assess the correlation between organisational culture, organisational commitment, and employee performance. The findings indicated that the organisational culture had a partially positive and statistically significant impact on the performance of employees within the HRD department at PT Agri First Indonesia. Additionally, it was observed that organisational commitment also had a partially positive and statistically significant influence on employee performance within the same department at PT Agri First Indonesia. The performance of employees at PT Agri First Indonesia is influenced by both organisational culture and organisational commitment concurrently. The research findings have practical applications that might aid firm management in identifying areas for change to enhance employee performance and overall organisational effectiveness.